2018
DOI: 10.23818/limn.37.09
|View full text |Cite
|
Sign up to set email alerts
|

Growth and age structure in captive and wild stocks of the endangered western ruivaco Achondrostoma occidentale (Cyprinidae)

Abstract: Growth and age structure in captive and wild stocks of the endangered western ruivaco Achondrostoma occidentale (Cyprinidae)Declines in freshwater fish populations are occurring at a fast rate, increasing the importance of ex-situ conservation programs supported by sound knowledge of population dynamics and life-history traits of the target species. We analysed the growth and age structure of wild and captive stocks of the western ruivaco Achondrostoma occidentale, a Portuguese endangered cyprinid, targeted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Cultured fish were longer, heavier and were more fecund than the wild fish. Similar results in other species have also shown cultured fish grew faster than the wild ones, such as western ruivaco Achondrostoma occidentale (Mameri et al, 2018), Atka mackerel Pleurogrammus monopterygius (McDermott et al, 2011), steelhead Oncorhynchus mykiss (Kostow, 2004), Atlantic salmon (Blanchet et al, 2008), gilthead sea bream Sparus aurata (Grigorakis et al, 2002) and brown trout (Hedenskog et al, 2002). O'Sullivan et al (2020) showed that the fecundity of cultured Atlantic salmon was approximately 1.4 times higher than wild ones.…”
Section: Discussionsupporting
confidence: 74%
“…Cultured fish were longer, heavier and were more fecund than the wild fish. Similar results in other species have also shown cultured fish grew faster than the wild ones, such as western ruivaco Achondrostoma occidentale (Mameri et al, 2018), Atka mackerel Pleurogrammus monopterygius (McDermott et al, 2011), steelhead Oncorhynchus mykiss (Kostow, 2004), Atlantic salmon (Blanchet et al, 2008), gilthead sea bream Sparus aurata (Grigorakis et al, 2002) and brown trout (Hedenskog et al, 2002). O'Sullivan et al (2020) showed that the fecundity of cultured Atlantic salmon was approximately 1.4 times higher than wild ones.…”
Section: Discussionsupporting
confidence: 74%
“…Spawning adult nase are easily accessible as they congregate to spawn. Nase larvae can be reared in ponds with a high rate of success, which makes supportive breeding and restocking a potentially valuable conservation tool for this species (Mameri et al, 2018; Lepič, Blecha & Kozák, 2019). However, supportive breeding can have a detrimental impact on the genetic diversity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the strong decline of many freshwater fish and mussel populations, ex‐situ conservation programmes, including captive breeding and restocking, are gaining increasing importance in their conservation (Targońska, Żarski & Kucharczyk, 2008; Roques et al, 2018; Lamothe & Drake, 2019; Lepič, Blecha & Kozák, 2019; Strayer et al, 2019; Manubens et al, 2020; Wetjen et al, 2020; Geist et al, 2021). A successful implementation of supportive breeding measures is particularly crucial if populations are declining very quickly or where species are not able to survive in natural habitats despite extensive in‐situ habitat restoration efforts (Mameri et al, 2018; Manubens et al, 2020). One example is the common nase, Chondrostoma nasus L. (subsequently referred to as nase), a key species of European river systems that was once very widespread.…”
Section: Introductionmentioning
confidence: 99%